Quality Management and Practices 2012
DOI: 10.5772/37294
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between ISO 17025 Quality Management System Accreditation and Laboratory Performance

Abstract: IntroductionInternational Organization for Standardization ISO 9000 is a general standard related to fundamentals of implementation of a quality management system. The aim of ISO 9000 is to implement quality management procedures by means of leadership, work instructions, documentation and record keeping. ISO 9000 standard does not determine the quality or performance level of the product or service. It deals with standardization of process management and improvement of an organization. The origin of ISO 9000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 14 publications
2
17
0
Order By: Relevance
“…H3 states that TQM practices have a positive impact on operational performance, with path coefficient 0.29 ( t =4.07). This shows that TQM has a weak impact on operational performance as compared to SCM practices (Sadikoglu and Temur, 2012). This may be true if a firm is passionate about CF, but does not align its information systems, inventory management and supplier relationships towards a desired operational performance.…”
Section: Resultsmentioning
confidence: 99%
“…H3 states that TQM practices have a positive impact on operational performance, with path coefficient 0.29 ( t =4.07). This shows that TQM has a weak impact on operational performance as compared to SCM practices (Sadikoglu and Temur, 2012). This may be true if a firm is passionate about CF, but does not align its information systems, inventory management and supplier relationships towards a desired operational performance.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, acquiring the ISO certifications contributes to successful TQM practices. ISO certification for the purpose of advertisement and marketing gimmick prevents the firms from implementing the TQM practices resulting in insignificant or negative effects on performance of the firm [77]. In addition, certified TQM firms can get more recognition and credibility in the market than non-ISO-certified TQM firms.…”
Section: Discussion Of the Analysesmentioning
confidence: 99%
“…The LPF of ISO/IEC 17025 accredited laboratories in Turkey was analyzed to find the impact of accreditation and the results revealed that the accreditation should focus on quality, reliability and accuracy of the reported results (Sadikoglu and Temur, 2012). Ratseou and Ramphal (2014) conducted a study to analyze the impact of ISO/IEC 17025 on the operational performance of both commercial and non-commercial laboratories in South Africa and the results showed that the accreditation did not improve the operational performance because good laboratory practices are already a part of the laboratory operations.…”
Section: Bij 247mentioning
confidence: 99%